Analisis Pengaruh Kebutuhan Ekonomi Keluarga Terhadap Pendapatan Tenaga Kerja Wanita (Studi Kasus di Industri Kulit Kota Surabaya) - Yuliawati, Nitami; Pratomo, Gigih (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2019)
The purpose of this study is to prove a significant effect simultaneously, partially, and the more dominant influence between the needs of food, shelter, education, health, entertainment, electronic devices, transportation equipment and communication equipment to the income of female workers in the Surabaya leather industry . This study uses quantitative methods and uses samples with the Cluster Random Sampling method. The data collection technique used in this study is by using interviews and questionnaires, then analyzed using the Cross Section multiple linear regression analysis approach. This study has a population of female workers in the Surabaya leather industry as many as 2000 people while the determination of the sample to be used in this study is determined by using the Slovin formula that is equal to 350 respondents. Food, shelter, education, health and entertainment needs affect the income of female workers. Whereas for electronic devices, transportation equipment and communication equipment does not affect the income of female workers. Basically the income of female laborers is not always focused on electronic devices, transportation equipment and communication devices but is also used for other needs